Childhood Cancer Pain: a Challenge for Health Professionals - Alexis Ramón Pineda González; Grettel Águila Calero; Anaelys Acosta Hernández (Revista Finlay)
Cancer in pediatric ages is an uncommon disease, however, in recent years its incidence and prevalence has increased considerably. The International Union Against Cancer notes that every year around 160 thousand children are diagnosed with cancer in the world and in Cuba approximately 300 new cases are diagnosed every year in children under 18. The problems confronted by children with cancer and their families are growing, which requires new and complex treatment strategies. The management of this type of pain is a great challenge for the medical staff, as it compels them to develop knowledge and skills for helping children who suffer.